Cournot Oligopoly, Homogeneous Products and Grappa Market: An Econometric Study - Laura Onofri; Vasco Boatto (Economics and Econometrics Research Institute (EERI), 2015)
In this study, using scanner data, collected from super-market transactions in 2009, we estimate an eight equations simultaneous model with a 3SLS routine, with the objective to empirically analyze the Grappa market structure. Results show that the supply side of the Grappa market is characterized by an oligopolistic structure, where the dominant firms compete as oligopolists à la Cournot with homogeneous products. Firms' competition is mostly played on the quantity grounds and mostly disregards product differentiation strategies. The dominant firms produce and supply a “cheap”, homogenous product. Interpretation of the results focus on cultural consumption of this very “ancient” liquor and corroborate previous studies, where hedonic analysis of the demand side has shown consumers' very low/null implicit prices for the product differentiated characteristics.
Keywords: L13; Q11; C3; 330; Cournot oligopoly; 3SLS; scanner data; grappa market